A Case of Prenatal Diagnosis of Turner Syndrome with Ultrasonography - Yusrawati, Yusrawati; Putri, Dona Mirsa (Fakultas Kedokteran Universitas Andalas, 2021)
Objective: To report a case of Turner syndrome diagnosed in prenatal care.Method: A case report.Case: Case of Mrs. Y 26-year-old woman G2P1A0L1 diagnosed on 19-20 weeks of gestation with Turner syndrome. Ultrasound examination findings were hydrops fetalis on the neck region, multiple septated cystic masses, subcutaneous edema, ascites, and hydrothorax. Subsequently, amniocentesis was performed and the chromosome analysis result showed Turner syndrome (45, X0). The patient was induced vaginal delivery on 22-23 weeks of pregnancy due to intrauterine fetal death indication. The baby was born with ambiguous genitalia, birth weight 500 grams, birth length 22 centimeters, and Apgar’s score was 0/0. The congenital anomalies discovered include subcutaneous edema, ascites, hydromacolly, and hydrops fetalis.Conclusion: Turner syndrome can be diagnosed at a prenatal period by ultrasound examination. Keywords: Turner Syndrome, Hydrops Fetalis, Ultrasonography